1958
DOI: 10.1161/01.cir.18.2.196
|View full text |Cite
|
Sign up to set email alerts
|

Sodium Chloride Excretion Following Salt Loading in Hypertensive Subjects

Abstract: Patients with essential hypertension show an altered renal excretory response to sodium chloride loading. Hypertensive patients acutely eliminate a greater proportion of a salt and water load than do normotensive subjects. This renal abnormality appears to be due to an augmented tubular rejection of sodium chloride and water. This study further defines the nature and extent of this alteration in electrolyte and water metabolism.A PREVIOUS study' confirmed the ob-,&-,Lservations of others2-9 that hypertensive p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0

Year Published

1960
1960
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(13 citation statements)
references
References 28 publications
2
11
0
Order By: Relevance
“…In contrast, our experiments demonstrated an enhanced ability to excrete an acute salt load in LSD1-deficient mice. This result is consistent with previous studies in humans, where low renin hypertensives hyperexcreted a salt load in contrast to normotensives or non-modulating hypertensives (a normal renin form of salt-sensitive hypertension) (Cottier et al 1958;Krakoff et al 1970;Luft et al 1977;Rydstedt et al 1986;Hollenberg et al 1986). In this study (data not shown) and previously (Pojoga et al 2011b), renin and aldosterone levels were suppressed in LSD1-deficient mice on HS diet, indicating that activation of the RAS is not a driving force for elevated blood pressure.…”
Section: Animal Studiessupporting
confidence: 93%
“…In contrast, our experiments demonstrated an enhanced ability to excrete an acute salt load in LSD1-deficient mice. This result is consistent with previous studies in humans, where low renin hypertensives hyperexcreted a salt load in contrast to normotensives or non-modulating hypertensives (a normal renin form of salt-sensitive hypertension) (Cottier et al 1958;Krakoff et al 1970;Luft et al 1977;Rydstedt et al 1986;Hollenberg et al 1986). In this study (data not shown) and previously (Pojoga et al 2011b), renin and aldosterone levels were suppressed in LSD1-deficient mice on HS diet, indicating that activation of the RAS is not a driving force for elevated blood pressure.…”
Section: Animal Studiessupporting
confidence: 93%
“…However, since in the clamped kidney of hypertensive rats the reabsorption of sodium and water along the loop is quite normal (12), a humoral factor of extrarenal origin is most unlikely. This view agrees with that of Cottier, Weller, and Hoobler (6). From studies on patients with essential hypertension, these authors thought it more likely that a rise in pressure within the renal vessels acts directly to augment the tubular rejection of sodium chloride and water.…”
Section: Methodssupporting
confidence: 85%
“…6. Parallel to these changes there was a progressive decline in fractional water and sodium reabsorption along Henle's loop.…”
Section: Methodsmentioning
confidence: 96%
“…This phenomenon has been repeatedly reported in patients with essential hypertension (1)(2)(3)(4)(5). Patients with hypertension caused by chronic glomerulonephritis (9, 10), Cushing's syndrome (4, 6, 7), pheochromocytoma (4), primary aldosteronism (8,11), and unilateral renal disease (10) have also been reported to have an exaggerated natriuretic response to acute salt loading, suggesting that elevated blood pressure could be a common denominator in this phenomenon.…”
Section: Discussionmentioning
confidence: 81%
“…That patients with essential hypertension have an exaggerated natriuretic response to the rapid intravenous administration of sodium is well established (1)(2)(3)(4)(5). Other hypertensive states have also been reported to exhibit an exaggerated natriuretic response to acute salt loading (4,(6)(7)(8)(9)(10)(11).…”
mentioning
confidence: 99%